Determinants of Islamic Banking Adoption Among Millennials in Indonesia: An Extended Diffusion of Innovation Perspective - Hafiz As'ad; Dedy Rachmad (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2026)
This study investigates the determinants of Islamic banking adoption among the millennial generation in Indonesia using an extended Diffusion of Innovation (DOI) framework. Despite Indonesia’s large Muslim population, Islamic banking penetration remains relatively low. By integrating core DOI attributes with trust and social influence, this research examines five key determinants: relative advantage, compatibility, knowledge, trust, and social influence. A quantitative explanatory approach was employed using survey data collected from 115 millennial customers of Islamic banks across Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that compatibility, knowledge, and social influence significantly and positively affect adoption intention, while relative advantage and trust show insignificant effects. The model explains 64.2% of the variance in adoption intention, indicating strong explanatory power. The study contributes to the Islamic banking literature by demonstrating that value congruence, literacy, and social context outweigh perceived economic benefits in shaping millennials’ adoption behavior.